Study of some virulence factors of Aeromonas Spp. isolated from stool samples of children with diarrhea - Talib Hashim, Saba; Nema, Mahmoud Mohammed (The Iraqi Journal of Veterinary Medicine, 2018)
Three hundred samples of stool were collected from children, who are suffering from diarrhea, during the period from October to December 2016 at Fatima Al Zahra and Shaheed al-Sadr hospitals. All bacterial isolates have been submitted to the cultural, microscopical, biochemical examinations, and Vitek 2 system identification to identify Aeromonas isolates. All the isolates under study were tested for their ability to the production of certain factors associated with virulence. It has been concluded that 12 (4%) of collected samples were positive to Aeromonas Spp. The virulence factors of Aeromonas spp. were detected and showed that all the isolates have the ability to produce haemolysin, protease, lipase, phospholipase, gelatinase enzymes, and biofilm on Congo red agar.